Dexmedetomidine attenuates hypoxia/reoxygenation injury in primary neonatal rat cardiomyocytes - Peng, Ke (Exp Ther Med, 2017)
Systemic administration of dexmedetomidine provides cardioprotection against ischemia/reperfusion (I/R) injury; however, the direct effects of dexmedetomidine on cardiomyocytes have not been clarified. The present study investigated the effects of dexmedetomidine on primary neonatal rat cardiomyocytes under hypoxic/reoxygenation (H/R) conditions. In order to simulate in vivo I/R injury, primary neonatal rat cardiomyocytes were cultured under hypoxic conditions for 1 h and subsequently reoxygenated for 24 h. The effects of preconditioning with dexmedetomidine 2 h before hypoxia and postconditioning during reoxygenation were also examined. Cellular viability and activity were analyzed by monitoring the dynamic response profile of living cells using a real-time cell analyzer system. A special scaled index, defined as the normalized cell index (NCI), was used to minimize the influence of inter-experimental variations. The dose-effect curve was generated from the area under the time-course curve values of NCI. H/R exposure markedly decreased cell viability and activity. Furthermore, no cytotoxicity was associated with a clinically relevant concentration of dexmedetomidine. Preconditioning with dexmedetomidine concentration-dependently ameliorated the reductions in NCI in cardiomyocytes following H/R injury. Additionally, postconditioning with dexmedetomidine improved the reductions in NCI at concentrations between 3 and 200 nM. Finally, the effect of 3–40 nM dexmedetomidine postconditioning was greater than preconditioning. These results indicated that preconditioning and postconditioning with dexmedetomidine attenuated H/R injury in primary neonatal rat cardiomyocytes at the cellular level.